A study of the hotline complaint service in Kuching City South Council with a view ot making it more effective through action research - Loh, Elizabeth. (1998)
This study was based on the assumptions that the current hotline service could be improved to render it more effective. It assumed that different complainants have different perception of good/excellent service and their needs and expectations may very with time. It also assumed that the effectiveness of the hotline might be influenced by the lack of service culture in the organization. The study was exploratory in nature using research. It is therefore assumed that the data collected and analyzed were valid reliable.